Komunikasi Strategis Special Event Kompetisi TIK dalam Membangun Citra Inklusif BAKTI Komdigi - Salsabila Shafa Widhi Sunoto; Nada Putri Naila; Anita Rosana (Jurnal Pustaka Komunikasi, 2026)
This study analyzes the role of a special event as a tool of government strategic communication in building an inclusive institutional image and supporting digital inclusion, through the 2025 ICT Competition for people with disabilities organized by BAKTI Komdigi. The study uses a qualitative approach with a case study method to understand how communication strategies are applied in a real context. Data were collected through interviews with key informants using purposive sampling. The results show that the special event was designed with clear communication goals to improve access, expand opportunities, and increase the confidence of people with disabilities in using digital technology. The meaning of inclusivity is built through participatory experiences, disability representation, and equal participation among stakeholders. As a result, an inclusive image is formed through real and continuous communication practices. The findings also show a clear division of stakeholder roles and the use of communication media to support public engagement, although there are still challenges in coordination and feedback management. This study fills a research gap, as most previous studies focus on the corporate sector, while this study highlights a government context. Theoretically, this study enriches strategic communication by showing that an inclusive image is shaped by the alignment of messages, actions, and stakeholder experiences.